Groundwater Contamination Due To Road De-icing Chemicals — Salt Balance Implications - Howard, Ken; Haynes, Janet (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Abstract Every year, roads and highways in Met-ropolitan Toronto receive more than100,000 tonnes (t) of NaCI road de-icingchemicals. While much of this salt isflushed from the region every winterseason by overland flow, a proportionwill enter the sub-surface and even-tually discharge to urban streams asbaseflow. To determine annual reten-tion rates of de-icing salts in an urbanwatershed, a chloride mass balancehas been applied to the Highland Creekbasin, a typical urban catchment ineastern Metropolitan Toronto. Thecatchment has an area of 104 km2 andgroundwater recharge is estimated to be 162 mm per year. Chloride input tothe catchment was determined frommunicipal records. These show that thecatchment receives approximately10,000 t of chloride annually, predomi-nantly in the form of NaCI de-icingchemicals which are applied to roads,highways and parking lots during thewinter months. Chloride output was es-timated from stream flow and electricalconductivity measurements recordedat 15-minute intervals over a two-yearperiod. The balance reveals that only 45% ofthe salt applied to the catchment isbeing removed annually and that theremainder is entering temporary stor-age in shallow sub-surface waters. Ifpresent rates of salt application aremaintained, it is predicted that averagesteady-state chloride concentrations inground waters discharging as springsin the basin will reach an unacceptable426 ± 50 mg-L"1 possibly within a 20-year time frame. The value of 426mg-L-1 represents a three-fold increaseover present average baseflow con-centrations, and is nearly twice thedrinking water quality objective of 250mg»l_-1 maximum acceptable concen-tration.